2022
DOI: 10.1098/rspb.2022.0548
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance vocalizations of spotted hyenas contain individual, but not group, signatures

Abstract: In animal societies, identity signals are common, mediate interactions within groups, and allow individuals to discriminate group-mates from out-group competitors. However, individual recognition becomes increasingly challenging as group size increases and as signals must be transmitted over greater distances. Group vocal signatures may evolve when successful in-group/out-group distinctions are at the crux of fitness-relevant decisions, but group signatures alone are insufficient when differentiated within-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
(136 reference statements)
1
7
0
Order By: Relevance
“…We showed that at large sample sizes, mean precisions and recalls across datasets increased by more than eight percentage points with this hierarchical approach (table 3). We found the accuracies of the hierarchical classifier on the largest balanced datasets to remain satisfactory and higher than most recent studies classifying animal vocalisations using MLAs [62,76,77], even though the number of samples per class of data was lower than those studies. The same was reflected in the performance of the hierarchical classifier on the originally collected calls (supplementary figure 2).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…We showed that at large sample sizes, mean precisions and recalls across datasets increased by more than eight percentage points with this hierarchical approach (table 3). We found the accuracies of the hierarchical classifier on the largest balanced datasets to remain satisfactory and higher than most recent studies classifying animal vocalisations using MLAs [62,76,77], even though the number of samples per class of data was lower than those studies. The same was reflected in the performance of the hierarchical classifier on the originally collected calls (supplementary figure 2).…”
Section: Discussionmentioning
confidence: 46%
“…We showed that at large sample sizes, mean precisions and recalls across datasets increased by more than eight percentage points with this hierarchical approach (table 3). We found the accuracies of the hierarchical classifier on the largest balanced datasets to remain satisfactory and higher than most recent studies classifying animal vocalisations using MLAs [62,76,77],…”
Section: Optimising Source Identificationmentioning
confidence: 53%
“…A thorough discussion is beyond the scope of this paper, but a more traditional representation based on performing a cepstral analysis at the middle of the call and adding delta and delta-delta coefficients performs worse (See S1 Text for more details). The better performance achieved with the bioacoustic set is consistent with the fact that the bioacoustic features are the cornerstone on which each call type is primarily defined by expert bioacousticians and primatologists (e.g., [87,89,90] for recent perspectives). Finally, the fact that the performance reached with the DCT set is almost as good as with the bioacoustic set is very encouraging: it indicates that a small number of acoustic descriptors succeed in capturing most of the relevant information present in the signal.…”
Section: Task 1: Identification Of Call Typessupporting
confidence: 60%
“…Acoustic variation among different individuals (signal strength) and consistency of individuals’ acoustic signatures over time (signal stability) are necessary for acoustic identification of individuals (AIID; Linhart et al 2022 ). If the acoustic variation quantified by Lehmann et al ( 2022 ) proves to be consistent over time, as suggested by East and Hofer ( 1991a ), then AIID could become a powerful tool for studying spotted hyenas.…”
Section: Future Directions In Methodologymentioning
confidence: 82%
“…The most vocal hyaenids, spotted hyenas, may be individually distinguishable not only through visual identification, but possibly through acoustic identification as well (Lehmann et al 2022 ). Spotted hyenas’ loudest vocalizations, called “whoops,” are emitted in bouts and can be heard from up to five kilometres away (Kruuk 1972 ; East and Hofer 1991a ).…”
Section: Future Directions In Methodologymentioning
confidence: 99%